Comparison of Chemical and Mechanical Prophylaxis of Venous Thromboembolism in Nonsurgical Mechanically Ventilated Patients. (22nd November 2015) - Gaspard, Dany; Vito, Karen; Schorr, Christa; Hunter, Krystal; Gerber, David
Abstract : Background. Thromboembolic events are major causes of morbidity, and prevention is important. We aimed to compare chemical prophylaxis (CP) and mechanical prophylaxis (MP) as methods of prevention in nonsurgical patients on mechanical ventilation. Methods. We performed a retrospective study of adult patients admitted to the Cooper University Hospital ICU between 2002 and 2010. Patients on one modality of prophylaxis throughout their stay were included. The CP group comprised 329 patients and the MP group 419 patients. The primary outcome was incidence of thromboembolic events. Results. Acuity measured by APACHE II score was comparable between the two groups (p = 0.215 ). Univariate analysis showed 1 DVT/no PEs in the CP group and 12 DVTs/1 PE in the MP group (p = 0.005 ). Overall mortality was 34.3% and 50.6%, respectively. ICU LOS was similar. Hospital LOS was shorter in the MP group. Multivariate analysis showed a significantly higher incidence of events in the MP prophylaxis group (odds ratio 9.9). After excluding patients admitted for bleeding in both groups, repeat analysis showed again increased events in the MP group (odds ratio 2.9) but this result did not reach statistical significance. Conclusion . Chemical methods for DVT/PE prophylaxis seem superior to mechanical prophylaxis in nonsurgical patients on mechanical ventilation and should be used when possible.